2019
DOI: 10.1038/s42256-019-0120-6
|View full text |Cite
|
Sign up to set email alerts
|

Consider ethical and social challenges in smart grid research

Abstract: Artificial Intelligence and Machine Learning are increasingly seen as key technologies for building more decentralised and resilient energy grids, but researchers must consider the ethical and social implications of their use Energy grids are undergoing rapid changes, requiring new ways both to process the large amounts of data generated from the power system, but also -increasingly -to take smart operational decisions [1].On the data side, the UK and most EU countries have committed to a target of offering a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…b diff C is the difference between community yearly bill considering network constraints and community yearly bill without network constraints as expressed in Eq. (33).…”
Section: ) Marginal Cost Redistribution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…b diff C is the difference between community yearly bill considering network constraints and community yearly bill without network constraints as expressed in Eq. (33).…”
Section: ) Marginal Cost Redistribution Methodsmentioning
confidence: 99%
“…Similarly, Seyfang et al [24] have conducted a detailed UKwide survey on energy community projects, and concluded that energy communities are diverse and rapidly growing. Recently, the modelling of energy community has gained increased attention from a social perspective focused on niche areas of: socio-technical energy system [25], social innovations and dynamics [26], socio-technical energy transitions [27], social entrepreneurship [28], grassroots innovation [29], multi-sectoral approaches [30], social acceptance and participation [31], social investments [32] and social factors in AI research [33]. Huang et al [34] have reviewed various simulation tools and models available for community energy system planning, design and optimization.…”
Section: Related Work a State Of Art In Energy Community Modellingmentioning
confidence: 99%
“…However, their development needs to be properly addressed. Some researchers emphasize the need to consider the ethical and social implications of these developments (Robu et al, 2019), and thus, artificial intelligence framework should pass through a regulatory process to enable sustainable development, otherwise, it could result in gaps in transparency, safety, and ethical standards (Vinuesa et al, 2020). But, from a technological perspective, as reported in (Strukov et al, 2019), artificial intelligence has made such huge steps forward that we have arrived at a scientific Frontier whereciting the authors -'artificial intelligence needs new hardware, not just new algorithm.'…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Transient dynamic behaviors for dynamically induced cascade failures have been studied by Schäfer et al (2018), highlighting the need for further investigation to outline failures propagation dynamics and mitigation strategies. Robu et al (2019), wisely highlighted the fundamental ethical and social challenges for the digital revolution which is irreversibly shaping the smart grid scenario. Conclusions suggest the need for a careful control for the design and realization of the smart grids, whose increasing architectural complexity and AI need to be properly ensured, to prevent, for instance, drastic blackouts.…”
Section: Robustness and Resiliencementioning
confidence: 99%
“…One current matter of considerable societal importance is the need for a complex multi-objective optimization of environmental objectives, energy security and energy equity [1][2][3]. This approach mirrors the wider need to optimize all subsurface energy source uses, recognizing benefits, costs and consequences.…”
Section: Introductionmentioning
confidence: 99%